(untitled) (Journal of Universal Science Research, 2025)
This thesis explores the English Romantic period, focusing on its major writers and their contributions to the literary canon. It examines the key themes, stylistic innovations, and philosophical underpinnings of Romantic literature, analyzing how prominent writers such as William Wordsworth, Samuel Taylor Coleridge, Lord Byron, Percy Bysshe Shelley, and John Keats shaped the movement. By investigating their works and the socio-historical context of the Romantic era, this study aims to provide a comprehensive understanding of the impact and legacy of English Romanticism.